Thematic Learning Design at SDN Kuta Bakmee - Ai sumini; Dhea amanda; Hasna Arifatul Haq; Merlina Agustin; Siti Mayang Sari; Lili Kasmini (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This study uses descriptive qualitative research, which is research based on phenomena observed by researchers in accordance with events that occurred at Kuta Bakmee State Elementary School. Based on the existing phenomenon, the research concluded that the learning carried out by teachers at SD Negri Kuta Bakmee as a whole has used the new Knowledge learning model, From the observations of the research found that in the Kuta Bakmee State Elementary School Banda Aceh has a special learning model model in the learning process which affects the character of students, related to this the teacher applies the learning model strategy in each high class corresponds to the subject to be delivered. Class teachers encourage student interaction and collaboration through group discussions, joint projects or classroom activities that promote cooperation. The data used in the study used primary data sources, which were obtained directly in the field by observation and interviews through informants, namely principals, teachers and several students in lower grades 1-2 SD Negeri Kuta Bakmee. This article focuses on thematic learning design, where there are several subjects combined into one theme, and how much the level of understanding of students in the learning design used